Peter Klepec - Moric, Anja (Ars et humanitas, 2015)
The narrative hero Peter Klepec is known (and laid claim to) by the inhabitants of the Čabranka-Osilnica valley, the border area on the Croatian and Slovenian side of the border. There circulate a number of quite similar stories about him, in which a frail illegitimate child Peter becomes a strong man, whose supernatural powers help the needy and drive the enemies from these regions. This paper shows the changing role and diversity of interpretations of myth in time and space using the example of folk and literary hero Peter Klepec. It focuses on the historical changes in the perception of Peter Klepec: namely, on his (local) function at the time of the Hapsburg imperial policy, the process of his nationalisation and dilemmas that arose following the division of the Čabranka-Osilnica area, i.e., the originating area of the creation of the legend of the two countries (Croatia and Slovenia). It shows that Klepec was due to different historical circumstances and (interpretive) discourse used for different purposes. First, he served as a symbol of strength and survival in the Čabranka-Osilnica valley, and then as the Hapsburg myth that justified the existence of the monarchy facing the hostile Ottomans, and lastly as an allegory of a servile Slovene, who is always just a faithful bondsman to other masters (first under the Austro-Hungarians and then the European Union).
Keywords: hero; Slovene literature; slovenska književnost; miti; myth; mythology; mitološki junaki; nationalism; nacionalizem; border; Peter Klepec